Cálculo de área na vida e na escola : possíveis diferenças conceituais - Santos, Laceni Miranda Souza dos (2010)
This study focuses on the discussion regarding mathematical knowledge involved in the work of rural farmers, the possible relations existing within the farmers‟ mathematical concepts, the social-cultural experience of students and the pedagogical practice of teachers of the rural Municipal Schools in the region of Irecê, BA, with respect to area calculation. The main objective was to investigate the practical mathematical knowledge of agricultural workers, specifically, area calculation, in order to establish possible conceptual differences between the informal conduct of rural workers and the formal conduct used in the school. The methodology used in this study was qualitative, as it evaluates the attitudes of the individuals in their social-cultural environment. The research was based on two distinct categories: one belonging to the school, comprising of students from Eighth and Ninth grades, and Math teachers; the other not being part of the school, represented by rural workers, all the residents of the city of Gameleira dos Crentes and the municipality of João Dourado, BA, situated in the micro-region of Irecê, Bahia. The theoretical references were taken from Ethnomathematics, as a possibility of interlocution between formal mathematical knowledge and knowledge stemming from everyday activities, as well as from the discussion of contributions of the social-cultural theory based on Vigotsky, on the anlaysis of concept development proposed by Vergnaud, by which the use of area calculation with fathoms, squares, acres and hectares can be considered in the context of this research, as theorems-in-action.